Service Marketing Ingredients of Small Resort Businesses in Nakhon Nayok Province - Chongngam, Maliwan (Dusit Thani College Journal, 2020)
The purpose of this research was to study the marketing mix of small resort businesses in Nakhon Nayok Province. In this research, quantitative research was designed by using questionnaires. The study indicated that tourists have an opinion on the marketing mix of the service market which are important to the business operation for a small resort business in Nakhon Nayok Province consisting of 3 main aspects which are the price aspect, the product aspect, the physical aspects. Therefore, in order for the resort to be well - known, entrepreneurs need to adjust operations plans or strategies in order to maintain the profitability of the business, study competitors’ room rates so that they are not higher than other operators, focusing on service quality products, giving special privileges for using other services of the resort. Physical characteristics are probably difficult to make changes but not difficult to make improvements which may currently be viewed as a professional aspect of resort management. The place is modern, beautiful, comfortable to live, and the reliability of the resort in order to maintain a profitable level. Entrepreneurs must try to reduce unnecessary costs and expenses without affecting the service to customers.